Evaluation of Correlation Between Serum Level of Dihydropyrimidine Dehydrogenase Enzyme and Capecitabine Induced Adverse Reaction - Elyasi, Sepideh; Allahyari, Abolghasem; Sheikhvanloo, Maryam; Jannati, Mahdi; Kalalinia, Fatemeh; Mohamadpoor, Amir Hoooshang (Reports of Radiotherapy and Oncology, 2018)
Background: Capecitabine is widely used to treat patients with gastrointestinal and breast cancers. However, its narrow therapeutic index is a limitation and prevents the achievement of a good therapeutic response. Dihydropyrimidine dehydrogenase (DPD) is the main enzyme in the metabolism of capecitabine. Previous studies show that deficiency in the activity of this enzyme can lead to incomplete metabolism of fluoroprimidine derivatives and severe complications. However, in the case of capecitabine, limited information based on case reports and small population surveys are available. There is also scarce evidence of a relationship between serum concentrations of DPD and the prevalence of capecitabine adverse reactions. Objectives: The current study aimed at investigating the relationship between DPD serum concentrations and capecitabine adverse reactions in patients with gastrointestinal tract cancer receiving capecitabine. Methods: The current cohort study was conducted on 30 patients referred to Isar Clinic affiliated to Mashhad University of Medical Sciences, Iran, diagnosed with gastric or colorectal cancer; treatment with capecitabine-containing regimens including XELOX (capecitabine + oxaliplatin) Or EOX (epirubicin + oxaliplatin + capecitabine) was performed from November 2016 to July 2017. At the beginning of the study, the patients’ demographic and laboratory data and information about the type of malignancy and chemotherapy regimen were recorded. Then, on the day before the first chemotherapy course administration until the end of the third cycle of chemotherapy, the side effects of the drug were investigated by interview, clinical examination, and laboratory findings. The occurrence of adverse reactions was assessed based on NCI-CTCAE V4 criteria. The serum concentration of DPD enzyme was measured by the enzyme-linked immunosorbent assay (ELISA) kit and its relationship with incidence of capecitabine induced side effects was evaluated. Results: A significant relationship was observed between DPD serum concentration and neuropathy (P < 0.001), thrombocytopenia (P = 0.017), neutropenia (P = 0.004), and weakness (P = 0.014). However, there was no significant relationship between DPD and other complications. No significant relationship was observed between age and gender of patients and DPD concentration (P > 0.05). Conclusions: According to the data obtained from the current study, the incidence of some of the capectiabine induced complications can be influenced by the serum concentration of DPD.